Kebijakan Moneter dalam Perspektif Islam - Sahrul (Journal of Economic and Islamic Research, 2024)
Monetary work in the context of Islamic economics which considers social justice and fraternity, in Islamic economics, monetary work does not only focus on supply and demand for money, it is also focused on the principles of fair trade and inclusion. Irnir is based on a conventional approach that often only considers price stabilization and economic growth. In the context of economics, monetary work in Islamic economics is intended to create economic stability in a way that considers the distribution of wealth and income in a balanced manner I'm here. This is not an important thing to prevent economic imbalances that can disrupt the social and economic balance in society. An artillery analysis methodology that uses a qualitative analysis approach with an integrated analytical analysis method helps to explain scientific concepts in depth. Derscrirptirf analysis allows authors to describe and explain the phenomena or concepts of dertairl based on the findings of the analysis. By implementing monetary work that takes into account the inequalities of justice and brotherhood, it is hoped that a country's economy can achieve stability sustainable paper, by considering the balance between circulating money and the number of goods and services available. Disbalance in environmental matters can cause serious economic disruptions. Jadir, it is important to understand that in an Islamic economic context, monetary work is not only about traditional macroeconomic stability, it is also about creating conditions that support social and economic stability the wider one